2017
DOI: 10.25115/ejrep.v8i21.1388
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence in Physical and Mental Health

Abstract: A lo largo de esta última década el interés por el estudio de la Inteligencia Emocional y su relación con la salud ha aumentado notablemente. El presente artículo tiene el objetivo de presentar los resultados de los estudios más relevantes que relacionan la Inteligencia Emocional medida como rasgo con las condiciones de salud física y mental. Los resultados indican que niveles altos de Inteligencia Emocional están significativamente relacionados con una buena salud mental mientras que niveles bajos de Intelige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
0
3
0
3
Order By: Relevance
“…Therefore, happiness cannot depend on their absence, but on a balance between the quantity and intensity of pleasant/unpleasant. In such a way, people who pay too much attention to their emotions and moods and do not have an adequate emotional clarity and repair would not be capable enough to understand and regulate the different emotional states [69,70,71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, happiness cannot depend on their absence, but on a balance between the quantity and intensity of pleasant/unpleasant. In such a way, people who pay too much attention to their emotions and moods and do not have an adequate emotional clarity and repair would not be capable enough to understand and regulate the different emotional states [69,70,71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that higher emotional intelligence can relieve stress and anxiety (21) and can improve people’s overall sense of life satisfaction (22). Furthermore, many studies have found that emotional intelligence has a significant and positive effect on inhibiting mental symptoms (23, 24). Therefore, we can hypothesize that emotional intelligence plays a mediating role in the effects of childhood maltreatment on mental symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effects of emotional intelligence, many researchers have investigated the relationship between emotional intelligence and mental health (Rosenstein & Stark, 2015). Emotional intelligence components could predict mental health (Martínez González et al., 2010). Meanwhile, analytical researches have shown emotional intelligence as one of the most important predictors of mental and physical health (Rosenstein & Stark, 2015).…”
Section: Introductionmentioning
confidence: 99%